Towards successful bottom-up transitions: Conceptualizing transformative capacities of individuals in social innovations - Tanja Kaufmann; Katharina Schiller; Linda Widdel (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2022)
In socio-technical transitions research, capacities relevant for transformations have primarily been assessed at systemic or niche levels, with capacities of individual actors to engage in transformative activities not yet well-conceptualized. This paper draws on theories of power in transitions, transformative social innovation and social practice theory to develop a conceptual framework for transformative capacities at the level of the individual citizen. We argue that in order to change social practices and foster successful bottom-up transitions, different forms of capacities - with regards to the elements of a social practice (meanings, competences and materials/resources) - are required. As a next step, the framework developed based on different literatures from transitions research and sociology will be tested empirically in an online-survey targeted at individuals engaged in social innovation. The objective is to better understand social processes of change and the conditions for them, in order to support the development of participatory governance models.
Keywords: 330